Políticas públicas com axé: religiões afro-brasileiras e a promoção da igualdade racial: (demandas para a educação do Recife) - Nascimento, Maria Cristina (2017)
This research aims to analyze the role of the Afro-Brazilian Religions in CPPIR (Conference of Racial Equality Policies) in Recife (from 2005 to 2013), concerning their demands to the public education in Recife. This is a qualitative study in which the people’s ideas and statements, the analyses of documents, the conference reports and the bibliographical research were used in order to help a better analysis of the advancements, difficulties and resistances in the implementation of public policies that are supposed to reduce historical injustices perpetrated by racism. To place the Afro-Brazilian religions in a historical context, we used the theoretical contribution of sociology, anthropology and history seeking to understand how they were structured in the past and how they are currently configured in Recife. We seek to establish a dialogue among the several forms of ways in which the religions of African matrices acts within the public sector. We take in consideration the black social movement, the women's movement and feminism, in the fight against racism and religious intolerance. Emancipatory and antiracist education are considered as fundamental tools to achieve the objectives, which are pending on the implementation of Laws 10.639 / 3 and 11.645 / 8.The discussion about racism and the struggle for rights of the black population are historically important to the Black Social Movement, especially in the questioning the ideal of racial democracy. Their demands for an education without discrimination, against racism and which includes Afro-Brazilian religions as one more element of identity and a milestone for their claims. As a result of the Racial Equality Conferences we can point the struggle for the Afro Brazilian religion to be recognized as a religion and the engagement to fight against religious intolerance and racism. All of them are present in the proposals made by people of the Afro-Brazilian religious and religious traditions. The issues are their main demands for a public education, committed to social, anti-racist transformations and which respects a plurality of religions.